2014
DOI: 10.1111/jce.12345
|View full text |Cite
|
Sign up to set email alerts
|

Long Pacing Pulses Reduce Phrenic Nerve Stimulation in Left Ventricular Pacing

Abstract: Long pulse durations lead to a decreased threshold of the heart relatively to the phrenic nerve and may prevent stimulation of the phrenic nerve in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The resulting strength duration curves demonstrated that the chronaxie of LV myocardium was higher than that of the phrenic nerve . In 3 patients, an unfavorable very small or zero margin was rendered higher to at least a factor of 2 . The largest change between the 2 thresholds was observed up to a pulse width of 1.5 milliseconds …”
Section: Editorial Commentmentioning
confidence: 90%
See 2 more Smart Citations
“…The resulting strength duration curves demonstrated that the chronaxie of LV myocardium was higher than that of the phrenic nerve . In 3 patients, an unfavorable very small or zero margin was rendered higher to at least a factor of 2 . The largest change between the 2 thresholds was observed up to a pulse width of 1.5 milliseconds …”
Section: Editorial Commentmentioning
confidence: 90%
“…During the implant procedure, LV and phrenic nerve capture thresholds were determined at varying pulse widths, from 0.3 to 2.9 milliseconds. In 9 of 11 patients, the LV threshold was reduced at a greater rate than the phrenic nerve threshold with increasing pulse width . The resulting strength duration curves demonstrated that the chronaxie of LV myocardium was higher than that of the phrenic nerve .…”
Section: Editorial Commentmentioning
confidence: 95%
See 1 more Smart Citation
“…In clinical studies, a threshold difference less than 3 V has been associated with clinically significant phrenic stimulation (19). Other strategies that have been reported in the literature include using leads with multiple electrodes allowing for reprogramming between electrodes (20), using closely spaced bipoles (21), and having longer pulse duration (22), although we did not attempt to replicate these findings for epicardial pacing or investigate whether they have incremental effect.…”
Section: Discussionmentioning
confidence: 99%
“…Another area where knowledge of strength-duration curves for the HB might play a role is the achievement of selective vs nonselective HB capture. A few studies reported that differences in chronaxie values enable selective pacing of different tissues from the same electrode by using a different combination of pulse widths and voltage output [12][13][14][15] ; whether this is also the case with HB/RV myocardium capture is not known.…”
Section: Introductionmentioning
confidence: 99%